Genomic Analysis of Sarcomyxa edulis Reveals the Basis of Its Medicinal Properties and Evolutionary Relationships - Tian, Fenghua; Li, Changtian; Li, Yu (Frontiers in Microbiology, 2021)
Yuanmo [Sarcomyxa edulis (Y.C. Dai, Niemelä & G.F. Qin) T. Saito, Tonouchi & T. Harada] is an important edible and medicinal mushroom endemic to Northeastern China. Here we report the de novo sequencing and assembly of the S. edulis genome using single-molecule real-time sequencing technology. The whole genome was approximately 35.65 Mb with a G+C content of 48.31%. Genome assembly generated 41 contigs with an N50 length of 1,772,559 bp. The genome comprised 9364 annotated protein-coding genes, many of which encoded enzymes involved in the modification, biosynthesis, and degradation of glycoconjugates and carbohydrates; or enzymes predicted to be involved in biosynthesis of secondary metabolites such as terpene, type I polyketide, siderophore, and fatty acids, which are responsible for the pharmacodynamic activities of S. edulis. We also identified genes encoding 1,3-β-glucan synthase and endo-1,3(4)-β-glucanase, which are involved in polysaccharide and uridine diphosphate glucose biosynthesis. Phylogenetic and comparative analyses of Basidiomycota fungi based on a single-copy orthologous protein indicated that the Sarcomyxa genus is an independent group that evolved from the Pleurotaceae family. The annotated whole-genome sequence of S. edulis can serve as a reference for investigations of bioactive compounds with medicinal value and the development and commercial production of superior S. edulis varieties.